Bending working law of corroded ductile iron pipe flange connections revealed by structural stressing state theory. (October 2022) - Zhao, Jianbin; Wang, Qi; Gong, Yanfa; Zhang, Yannian; Zhou, Guangchun
Abstract: Applying structural stressing state theory, this study finds out the bending working law of corroded ductile iron pipe flange (CDIPF) connections from their tested strain data. Firstly, the strain data are transformed into the generalized strain energy density values to build the stressing state mode and the characteristic parameter. Then, the Mann-Kendall criterion is used to detect the mutation points in the evolution curves of the stressing state characteristic parameters with the load increase according to the natural law from quantitative change to qualitative change of a system. Meanwhile, it is verified that the evolutions of the stressing state modes also present the corresponding mutation features. The mutation points define the starting points of the bending CDIPF connections' failure processes. Furthermore, the Mann-Kendall criterion distinguishes the elastoplastic branch (EPB) points in the normal working processes of CDIPF connections. Both the failure starting point and the EPB point lay the new foundation to analyze the working performances of the CDIPF connections and to improve their design. Highlights: Uncover the essential working law of CDIPF connections from the tested data using structural stressing state analysis. Reveal the essential bending strength of CDIPF connections under different corrosion conditions. Reveal the elastoplastic branch feature in the bending working processes of CDIPF connections.